RGD v2.0: a major update of the ruminant functional and evolutionary genomics database. Issue Volume 50:Issue D1(2022) (13th October 2021) - Fu, Weiwei; Wang, Rui; Nanaei, Hojjat Asadollahpour; Wang, Jinxin; Hu, Dexiang; Jiang, Yu
Abstract: Ruminant Genome Database (RGD; http://animal.nwsuaf.edu.cn/RGD ) provides visualization and analysis tools for ruminant comparative genomics and functional annotations. As more high-quality ruminant genome assemblies have become available, we have redesigned the user interface, integrated and expanded multi-omics data, and developed novel features to improve the database. The new version, RGD v2.0, houses 78 ruminant genomes; 110-species synteny alignments for major livestock (including cattle, sheep, goat) and wild ungulates; 21 012 orthologous gene clusters with Gene Ontology and pathway annotation; ∼8 600 000 conserved elements; and ∼1 000 000 cis -regulatory elements by utilizing 1053 epigenomic data sets. The transcriptome data in RGD v2.0 has nearly doubled, currently with 1936 RNA-seq data sets, and 155 174 phenotypic data sets have been newly added. New and updated features include: (i) The UCSC Genome Browser, BLAT, BLAST and Table Browser tools were updated for six available ruminant livestock species. (ii) The LiftOver tool was newly introduced into our browser to allow coordinate conversion between different ruminant assemblies. And (iii) tissue specificity index, tau, was calculated to facilitate batch screening of specifically expressed genes. The enhanced genome annotations and improved functionality in RGD v2.0 will be useful for study of genome evolution, environmental adaption, livestock breeding and biomedicine.